Steels : from materials science to structural engineering - Sha, Wei (Springer, 2013)
This book combines steels research and model development, including the application of modeling techniques in steels. Coverages structural engineering modeling and novel, prototype alloy steels such as heat-resistant steel and low nickel maraging steel